Livin' on the edge: reducing infanticide risk by maintaining proximity to potentially less infanticidal males - Penteriani, Vincenzo; Kojola, Ilpo; Heikkinen, Samuli; Find'o, Slavomír; Skuban, Michaela; Fedorca, Ancuta; García-Sánchez, Pino; Fedorca, Mihai; Zarzo-Arias, Alejandra; Balbontín, Javier; Delgado, María del Mar (Animal Behaviour, 2024)
© 2024 The Authors. Published by Elsevier Ltd on behalf of The Association for the Study of Animal Behaviour. This is an open access article under the CC BY-NCND license (http://creativecommons.org/licenses/by-nc-nd/4.0/) Infanticide is a significant evolutionary force influencing carnivore behaviours, as it is one of the primary contributors to offspring mortality. Female multimale mating, which creates paternal uncertainty, is known to reduce infanticide. We propose that two crucial steps are needed for this strategy to work in solitary species like brown bears, Ursus arctos. First, after mating, females should choose dens within their mating area (step 1), boosting the chances of encountering potential fathers of cub(s) after den emergence in spring. However, the efficacy of this strategy hinges on males' fidelity to the same mating areas from one year to the next (step 2). Our study confirmed that pregnant females consistently selected dens within their mating areas, with significant overlap (around 90%) between areas used by females with cubs and their mating zones. Males also demonstrated fidelity (over 65%) to mating areas over 2 consecutive years. Infanticide significantly shapes the sociospatial ecology of female brown bears, a phenomenon that can carry nutritional costs for females with cubs, and influence settlement patterns near human shields to increase reproductive success. Additionally, in hunted populations, removing resident males can trigger an influx of potentially infanticidal bears from elsewhere. V.P., J.B. and A.Z.-A. were financially supported by the I + D + i Project PID2020-114181GB-I00 funded by MCIN/AEI/10.13039/501100011033 and by the European Union. A.Z-A. was also financially supported by a Margarita Salas contract financed by the European Union (NextGenerationEU, Ministerio de Universidades y Plan de Recuperacion, Transformacion y Resiliencia) through the call of the Universidad de Oviedo (Asturias). The Finnish Ministry of Agriculture and Forestry financially supported Ilpo ...